Potential Adverse Drug Events and Nephrotoxicity Related to Prophylaxis With Omeprazole for Digestive Disorders: A Prospective Cohort Study - Varallo, Fabiana Rossi [UNESP]; de Nadai, Tales Rubens; de Oliveira, Alice Rosa Alves [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (Elsevier, 2018)
Purpose: The purpose of this study was to assess whether prophylaxis for digestive disorders with omeprazole is a risk factor for adverse drug events (ADEs) and kidney impairment. Methods: This was a 9-month, prospective, double-blinded cohort study performed in a Brazilian public hospital. All inpatients 18 years or older admitted during the period of data collection were divided into 2 cohorts. The first group comprised 200 patients receiving prophylaxis for digestive disorders with omeprazole. A total of 54 inpatients who received treatment with omeprazole and whose indication was not approved by the Brazilian Sanitary Agency and the US Food and Drug Administration were excluded. The second group comprised 219 inpatients without a prescription for omeprazole. Follow-up was performed until discharge and included assessment of medical records, medical prescriptions, laboratory data, and pharmaceutical anamnesis. The primary end point was kidney impairment. The variables monitored were kidney function (serum creatinine and urea levels as well as glomerular filtration rate), hepatic function (alanine aminotransferase and aspartate aminotransferase levels), pharmacotherapy, magnesium levels, and imputation of ADEs. With the aid of algorithms of World Health Organization and the National Coordinating Council for Medication Error Reporting and Prevention, we assessed the causality of adverse drug reactions (ADRs) and the seriousness of medication errors (ADEs), respectively. Findings: Prophylaxis for digestive disorders with omeprazole (P = 0.019) and sex (P = 0.010) were considered risk factors for increased serum creatinine level via multivariate logistic regression even with concomitant use of nephrotoxic drugs (P = 0.252). Six ADEs related to omeprazole were identified: 2 ADRs (1 possible and 1 definite), 2 medication errors (nonserious), 1 therapeutic failure, and 1 drug-drug interaction. Implications: Prophylaxis for digestive disorders with omeprazole and male sex may contribute to the development of kidney impairment because both result in increased serum creatinine levels. Therefore, pharmacotherapeutic follow-up of male patients diagnosed with kidney disorders should be considered to identify potential drug-drug interactions early. This follow-up can prevent worsening clinical conditions and/or contraindicate prophylactic use of omeprazole. ClinicalTrials.gov identifier: NCT02278432.
Keywords: adverse drug events; kidney impairment; omeprazole; pharmacovigilance; risk management